Contribuição ao estudo do desempenho de estacas do tipo raiz - Lima, Diana Rodrigues de (2014)
During the execution of the foundations of a building, commonly checks load capacity employing specific methods which vary depending on the type of stake, which is called evaluation of foundation performance. To stakes control is, generally made based on load test. This paper proposes a formulation for empirical prediction type of the root cuttings carrying capacity obtained by some variables monitored during their execution using a speedometer digital. For that were made slow static load tests in three root cuttings monitored at 350 and 410 mm. Several combinations of the parts of the peak load capacity and the side and monitored variables were tested, using computer programs Excel and Maple. It was later sought an expression for predicting the tensile strength of the tested cuttings as a function of the variables monitored, according to relations of type polynomial, exponential, logarithmic and combination linear, with reference to the value obtained according to the method of the ABNT NBR 6122: 2010. It was found that there is a correlation between the load and the variables monitored. The variables that best fit the correlation were spin and speed advance. The results obtained with the expression proposed were consistent with the values reference to the tested cuttings. The method of Lizzi (1982) presented estimates more consistent with the results obtained in the form proposed that correlates capacity load and variables involved in enforcement proceedings.